学会員の知を結ぶ学会活動支援システム - 倉橋, 節也; 大塚, 雄吉; 寺野, 隆雄; 久川, 雅志 (横幹, 2008)
This article describes Gakkai Net, which is a general web-based platform, to support various activities of academic societies. Gakkai Net platform is designed to cover such various activities of academic societies as regular conference management, paper review, journal editing and production management, and membership administrations all on the web. The platform is characterized by the following unique features: 1) Database centered system, which contains various aspects of society members’ information, 2) Software agent sub-systems to facilitate the implementation of the functionalities, 3) Web-based applications for end-users with unified interfaces corresponding to the user model and access control for different types of users in order to comfort ever changing members in charge of activities. The article addresses the basic principles, system configuration and functions, current status, and future plans of Gakkai Net.